Synthesis of Unsymmetrical Mono- and Bissquaramides with (3-Aminopropyl)triethoxysilane (APTES) or Dopamine Moieties - López, Kenia A.; Piña, M. Nieves; Morey, Jeroni (Synlett, 2012)
A simple and efficient synthesis of unsymmetrical mono- and bissquaramides derivatives and their corresponding methyltrialkyl ammonium salts was achieved in moderate yields from diethyl squarate via sequencial reactions.
Keywords: squaramides; bissquaramides; modular synthesis; ammonium iodide salt; receptors